Metachronous small bowel adenocarcinoma after rectal adenocarcinoma: A case report. Issue 40 (8th October 2021) - Zhen, Ya'nan; Li, Jianqi; Wang, Ruogu; Lu, Shoutang; Zhou, Yongshun; Xiao, Ruixue
Abstract: Rationale: Small bowel adenocarcinoma (SBA), an uncommon gastrointestinal malignant tumor, is difficult to diagnose at an early stage because of its non-specific disease presentation. Metachronous SBA is a special type of SBA that is rarely reported. We herein report a case of metachronous primary SBA following resection of rectal adenocarcinoma. Patient concerns: A 65-year-old man presented to our hospital after having experienced recurrent bowel obstruction for 6 months. He had undergone a Dixon operation 30 months previously followed by adjuvant chemotherapy with capecitabine plus oxaliplatin. Diagnosis: Abdominal computed tomography showed thickened bowel walls in the right lower abdomen, and the patient was initially misdiagnosed with intestinal adhesion. After the operation, he was diagnosed with primary SBA (T3N0M0, stage IIA). Interventions: Treatment with a transnasal ileus tube was ineffective. Therefore, we performed small intestinal segmental resection and side-to-side anastomosis through open surgery. Outcomes: The patient completed all postoperative adjuvant chemotherapy, and posttreatment surveillance revealed no further abnormalities. Lessons: This case suggests that patients with colorectal adenocarcinoma may have an increased risk of metachronous SBA. Corresponding symptoms in high-risk patients should raise clinicians' suspicion for SBA, and further detailed examinations are imperative. Early screening for SBA may help to improve the patients' prognosis.